Seasonal Migration to Mitigate Income Seasonality : Evidence from Bangladesh - Khandker, Shahidur R. (Taylor and Francis, 2013)
In north-west Bangladesh, some 36 per cent of poor households migrate every year during the lean (monga) period to cope with seasonal deprivation. Analysis of household survey data shows that the probability of seasonal migration is high for households with a high dependency ratio, high dependency on wage employment, and in villages with high unemployment; but low in villages with microcredit access. Findings show that seasonal migration helps households to smooth consumption and that non-migrant households who suffer during monga would likely benefit from deciding to migrate. But the cost of migration and lack of networking are potential barriers.